TECHNOLOGY OF AN ENVIRONMENTALLY SAFE GAS CHEMICAL COMPLEX FOR UTILIZATION OF SULFUR-CONTAINING AND FLARE GASES DISCHARGED FROM TECHNOLOGICAL INSTALLATIONS - PhD Khuzhakulov A.F; PhD Akhmedova O.B.; Rakhimov Z.Z.; Khairullaev M.Z.; Khamroev F.B. (American Journals, 2023)
A schematic diagram of an environmentally safe HCG is presented, which provides practically waste-free processing of sulfur-containing natural gas.